Sustainable Development Comparative Analysis on State Banks and Regional Development Banks: Study Case in Indonesia - Ahmad Hidayat Sutawidjaya (Clean and Sustainable Production, 2023)
The COVID-19 pandemic that hit the world has impacted the performance of optical retail sales. This forces management to adapt to the changes that are taking place. One of them is to improve the service according to customer expectations. Analyzes were performed using internal and external methods. The internal method uses a fishbone diagram and the external method uses a Servqual analysis and a significance performance matrix. Research methodology will be conducted through observation, literacy studies, focus group discussions, and a survey of 100 respondents who are customers of optometrists. Survey results indicated that customer segmentation, time savings, incentive programs, and many customers switching to online sales were the main factors in the decline in sales. The gap in the dimension of empathy is the largest, and the priorities for service improvement are product price, prescription lens manufacturing process, product quality, and product warranty service.